Separating homeologs by phasing in the tetraploid wheat transcriptome - Krasileva, Ksenia V.; Buffalo, Vince; Bailey, Paul; Pearce, Stephen; Ayling, Sarah; Tabbita, Facundo; Soria, Marcelo; Wang, Shichen; Akhunov, Eduard D.; Uauy, Cristobal; Dubcovsky, Jorge; IWGS Consortium (My University, 2013)
Background: The high level of identity among duplicated homoeologous genomes in tetraploid pasta wheat presents substantial challenges for de novo transcriptome assembly. To solve this problem, we develop a specialized bioinformatics workflow that optimizes transcriptome assembly and separation of merged homoeologs. To evaluate our strategy, we sequence and assemble the transcriptome of one of the diploid ancestors of pasta wheat, and compare both assemblies with a benchmark set of 13,472 full-length, non-redundant bread wheat cDNAs. Results: A total of 489 million 100 bp paired-end reads from tetraploid wheat assemble in 140,118 contigs, including 96% of the benchmark cDNAs. We used a comparative genomics approach to annotate 66,633 open reading frames. The multiple k-mer assembly strategy increases the proportion of cDNAs assembled full-length in a single contig by 22% relative to the best single k-mer size. Homoeologs are separated using a post-assembly pipeline that includes polymorphism identification, phasing of SNPs, read sorting, and re-assembly of phased reads. Using a reference set of genes, we determine that 98.7% of SNPs analyzed are correctly separated by phasing. Conclusions: Our study shows that de novo transcriptome assembly of tetraploid wheat benefit from multiple k-mer assembly strategies more than diploid wheat. Our results also demonstrate that phasing approaches originally designed for heterozygous diploid organisms can be used to separate the close homoeologous genomes of tetraploid wheat. The predicted tetraploid wheat proteome and gene models provide a valuable tool for the wheat research community and for those interested in comparative genomic studies.
Citation: Krasileva, K., . . . & Dubcovsky, J. (2013). Separating homeologs by phasing in the tetraploid wheat transcriptome. Genome Biology, 14(6), 1-19. https://doi.org/10.1186/gb-2013-14-6-r66
Keywords: Transcriptome assembly; Multiple k-mer assembly; Wheat; Polyploid; Triticum urartu; Triticum turgidum; Pseudogenes